Pertumbuhan dan kelangsungan hidup benih ikan black ghost (Apteronotus albifrons) pada jenis pakan yang berbeda - Nur Abyan, Muhammad Faraz; Swasta, Ida Bagus Jelantik; Martini, Ni Nyoman Dian (e-Journal BUDIDAYA PERAIRAN, 2025)
The black ghost fish (Apteronotus albifrons) is a freshwater ornamental fish with a distinctive knife-like shape (Knife fish). Its unique shape makes it have high economic value in the market. However, the growth rate and high mortality of this fish are obstacles for cultivators. The main focus of this study was to determine the effect of providing different types of feed on the growth and survival of black ghost fish (A. albifrons) seeds. The study was conducted at the Mina Mustika Fish Farming Group, Bekasi City, for 45 days using a Completely Randomized Design (CRD). The treatment consisted of three types of feed, namely natural feed (Tubifex sp.) (P1), a combination of natural feed (Tubifex sp.) + commercial feed (PF100) (P2), and commercial feed (PF100) (P3), with three replications in each treatment. The parameters observed were absolute length growth, absolute weight, specific growth rate (SGR), and survival rate (SR). The measurement of water quality parameters was carried out as a form of attention to supporting factors for the study. The findings showed that the combination feed treatment (P2) provided the highest growth in length, weight, and specific growth rate with absolute length values ​​(4.36 cm), absolute weight (3.73 gr), and SGR (4.67%), followed by natural feed (P1) providing absolute length (4.09 cm), absolute weight (3.39 gr), and SGR (4.54%), and the lowest commercial feed (P3) providing absolute length (3.37 cm), absolute weight (2.50 gr), and SGR (3.91%). The highest survival rate (SR) was found in the natural feed treatment at 94%, followed by commercial feed at 93%, and combination feed at 91%. In general, water quality during the research period was in the optimal range to support the growth and survival of black ghost fish (A. albifrons) seeds. Keywords: Tubifex sp., natural feed, commercial feed, combination feed, aquaculture intensive